UNSUR SERAPAN ASING PADA JUDUL-JUDUL BERITA DI HARIAN KOMPAS - Kuswarini, Prasuri (Universitas Hasanuddin, 2015)
This article reviews the results of a small study of how often the absorption of foreign language used in the headlines of the newspaper KOMPAS, and whether the use of the the absorption in accordance with the rules of bahasa Indonesia, as well as needed or not.The method used in this study is qualitative. Data in the form of headlines were collected from KOMPAS, edition of March 2010. The analysis is based on the rules of the absorption of foreign language in bahasa Indonesia, and based on objective assessment whether the use of absorbed foreign words can meet or even exceed the limits of reasonableness.The results showed: the frequency of the use of absorbed words at the headlines of KOMPAS is very high, but still in accordance with the spelling rules of bahasa Indonesia.Keywords: headline, news, absorption elements, rules, fairness